CLOSED-LOOP SUPPLY CHAIN WITH DELIVERY LEAD TIME ON DIRECT AND INDIRECT CHANNEL - Sulastri, Endang; Setiyowati, Ririn; Siswanto, Siswanto (PATTIMURA UNIVERSITY, 2020)
The responsbility of protecting the environment rest with all parties, including manufacturers. Therefore, manufacturers reprocess their used products. Mathematically, it can be explained by closed-loop supply chain (CLSC) model. CLSC is a system that is carried out recycling or remanufacturing. In this study, closed-loop supply chain involves manufacturer and two retailers. Manufacturers sell their product directly to consumers and indirectly through retailers. The purpose of this study is to construct an optimal profit function of each actor. With centralized system, the model is a function of price without constraints by notice delivery lead time. The result shows that delivery lead have an impact to profit each actor. The longer delivery lead time decreases the profit.